2010
DOI: 10.1007/s12289-010-0797-x
|View full text |Cite
|
Sign up to set email alerts
|

FE simulation of micro-extrusion of a conical pin

Abstract: Successful forming of metal micro-components requires careful design of the process to make it suitable for uniform material flow, small-scale tooling and limited handling capability. FE simulation can be helpful in identifying the best process configuration before engaging in expensive experimental trials. It was used to study material flow, required force and tool contact stress in micro-extrusion of a single conical pin. Different process configurations (forward vs. backward extrusion), tool geometries (pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Similarly, they observed that lateral flow is higher in CG as compared with UFG material. Flow of material in backward extrusion is more than in forward extrusion [92] for UFG material.…”
Section: 2dmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, they observed that lateral flow is higher in CG as compared with UFG material. Flow of material in backward extrusion is more than in forward extrusion [92] for UFG material.…”
Section: 2dmentioning
confidence: 99%
“…Either decreasing specimen size or increasing grain size results in decrease of fracture toughness [95]. According to Rosochowska et al [92], formation of micro-pin of 0.15-mm diameter using A1070 UFG alloy led to shear localization and fracture. Fracture stress in material increases with a positive slope (grain boundary zone [ grain interior) and decreases with negative slope (grain boundary zone \ grain interior) while fracture toughness in zero slope condition is independent of grain boundary as shown in figure 30 [94].…”
Section: 2fmentioning
confidence: 99%
“…In short, the authors have highlighted the effect of size, parameter settings, and combinations of parameter settings in microextrusion processes. Rosochowska et al (2010) carried out finite element analysis of the microextrusion of conical pins whose larger diameters were 340 mm. They compared the performance of ultra-fine-grained material with that of coarse-grained material.…”
Section: Parametric Study and Modeling Of Microextrusionmentioning
confidence: 99%
“…Finite element (FE) simulation is a tool that can assist greatly in this effort. However, FE simulation of microforming processes has always been a challenge due to different types of size effects occurring in such length scale [21,55,102,136,137,179]. One such challenge is to define the correct friction factor, so that FE simulation results can match the experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, design and optimization of such processes require mathematical modeling before experimental tests. However, the discussed challenges make it difficult to predict the real material behavior during the process via simulation and modeling [136].…”
Section: Micro-extrusion Using a Sheet Metal As A Feed-strokementioning
confidence: 99%